Revisão de pesquisas básicas sobre controle aversivo em humanos - Powys, Gabriela Lembo Dias (2018)
Aversive control is a controversial area of study within Behavioral Analysis, especially when humans are used as experimental subjects. This work sets out to review basic studies into aversive control with humans that took place within the last 11 years. Specifically, this work aims to: (a) analyze and characterize basic studies that used human beings as participants and used aversive stimulus in the period between 2007 and 2017, focusing on details of the method used; (b) identify whether the author(s) justified or tested the aversive stimulus/stimuli used; (c) identify whether the author(s) name/comment on/evaluate the byproducts of aversive control; and (d) identify whether the author(s) make any ethical comments on the use of aversive stimulation with humans. Articles, theses and dissertations from Brazil and abroad conducted between 2007 and 2017 on online platforms were selected. These include 129 works, of which 35 were conceptual/historical/revisions, 37 applied studies and 57 basic studies – the latter were read in their entirety. The index of agreement between the researcher and the independent observer was 98.7%. Results indicate that the most commonly studied modality of aversive control is avoidance, participants used are generally typical adults, most experimental activities are conducted using a computer, and the aversive stimuli used as US are mainly auditory stimuli. In many studies analyzed, the authors substitute the unconditioned aversive stimulus used in studies with non-human animals with conditioned stimuli, although the results of some experiments which took this approach did not succeed in reproducing the results found in animal literature. Furthermore, a significant divergence was observed in the use and detailing of the description of certain kinds of aversive stimulation (conditioned and unconditioned) in basic studies with humans. It was confirmed that few basic studies refer to the byproducts of aversive control, or present ethical discussions related to this kind of control